Surgical techniques and prognostic nomogram for patients with supravalvular aortic stenosis - Yuekun Sun; Lizhi Lv; Xinyue Lang; Aihua Zhi; Simeng Zhang; Cheng Wang; Qiang Wang (European Journal of Medical Research)
Abstract Background An effective prognostic nomogram to predict the prognosis for supravalvular aortic stenosis (SVAS) patients is lacking. Methods A multi-center retrospective study of consecutive SVAS patients with surgery between 2002 and 2020 was conducted. Patients underwent McGoon repairs, Doty repairs, and other repairs. The primary outcome was the re-operation or restenosis at follow-up. The nomogram based on Cox regression and Kaplan–Meier method was used to show the risk factors of the primary outcome. The predictive accuracy was determined by the concordance index (C-index) and calibration curve. The results were validated using the bootstrap resampling method. Results Of the 291 SVAS patients, 143 (49.1%) used McGoon repairs, 118 (40.5%) used Doty repairs and 30 (10.3%) used other repairs. The median age at operation was 4.9 years (IQR 2.3–9.9). After a median follow-up of 24 months (IQR 6.0–54.0), no difference in re-operation or restenosis was found between McGoon repairs and Doty repairs. Age, gender, SVAS type, pulmonary artery stenosis, aortic valve stenosis, sinotubular junction z-score and gradient were considered independent risk factors by Lasso regression and were included in the nomogram. The C-index of the nomogram was 0.71 (95% CI 0.61 to 0.81). The calibration curve for the probability of re-operation or restenosis showed good agreement between prediction by nomogram and actual observation. Conclusions McGoon repairs and Doty repairs had no difference in re-operation and restenosis risk. The proposed nomogram gave an accurate prediction of re-operation or restenosis for patients with SVAS after surgery. Trial registration http://www.chictr.org.cn , ChiCTR2300067851, 2023.01.29 (retrospectively registered).